Spiritual medicine in the multi perspective of religion - Marwa Minhas; Syaefudin Ali Akhmad; Nadeem Afzal (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2017)
Spiritual healing, also known as healing through prayer and meditation, has been widely studied by various scholars from different religions including Islam, Hindu, Buddhism and Christianity. The term spiritual medicine is increasingly popular with increasing mental disorders, degenerative diseases, metabolic, cancer and social illness such as drug abuse. Religions of Islam, Hinduism, Buddhism and Christianity have almost the same tradition in the spiritual aspect to create purity of self and inner peace through the practice of worship or prayer based on spiritual meditation. The application of spiritual medicine is mostly done to reduce stress and anxiety due to illness suffered by the patient. Spiritual medicine is commonly used to peace building, study self-control, anger management, empathy, affection, calmness, and also to sharpen brain activity and increase well being. Spirituality refers to the process of improvement done with the aim to restore humans to the true figure as a God creation and have the correct perception about the true image of god based on the holy book of the Qur'an, Torah, gospel and the main figure of world religions such as the Buddha and prophet of Muhammad PBUH. All religions teach the need to ask the Creator to be healthy, prosperous and free from the sufferings of illness. The benefits of spiritual medicine depend on the quality, intensity and frequency or quantity of practices or methods that are practiced by each religious believer.